(untitled) (Journal of the College of Basic Education, 2023)
The emergence of multi-drug resistant bacteria to common antibiotics and their rapid increase are major health problems; many antibiotics have become less and less effective against pathogenic bacteria, therefore there is an urgent need to search for new antibacterial substances especially from natural sources. Many studies showed that herbs may positively affect microbial susceptibility to antibiotics. In this study, the combination effect of curcumin with Amoxicillin against different pathogenic bacteria (S. aureus, Streptococcus, E. coli, Pseudomonas, and Proteus) was investigated, using well diffusion method. The results indicate that curcumin has a synergistic, antagonistic and indifference effect when added to different concentrations of Amoxicillin against pathogenic bacteria. Synergistic response was 70%, indifference 20%, and antagonistic was 10%. The results revealed that curcumin improved the bactericidal effect of the antibiotic and has potentials in combination therapy against different pathogenic bacteria.